2007
DOI: 10.1111/j.1551-2916.2007.02046.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbothermal Reaction of Silica–Phenol Resin Hybrid Gels to Produce Silicon Nitride/Silicon Carbide Nanocomposite Powders

Abstract: A carbothermal reaction of silica–phenol resin hybrid gels prepared from a two‐step sol–gel process was conducted in atmospheric nitrogen. The gels were first pyrolyzed into homogeneous silica–carbon mixtures during heating and subsequently underwent a carbothermal reaction at higher temperatures. Using a gel‐derived precursor with a C/SiO2 molar ratio higher than 3.0, Si3N4/SiC nanocomposite powders were produced at 1500°–1550°C, above the Si3N4–SiC boundary temperature. The predominant phase was Si3N4 at 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…In the alumina foam, the formation of SiC was never confirmed by XRD, but it was assumed to be present, in accordance to what observed in numerous studies for bulk materials . Because the gas evolution of SiO or CO occurs in a limited fashion in bulk materials, the reaction with lower free energy change can occur.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In the alumina foam, the formation of SiC was never confirmed by XRD, but it was assumed to be present, in accordance to what observed in numerous studies for bulk materials . Because the gas evolution of SiO or CO occurs in a limited fashion in bulk materials, the reaction with lower free energy change can occur.…”
Section: Resultssupporting
confidence: 80%
“…The SiO, CO, and N 2 gases could directly react with each other to form Si 2 N 2 O via a gas phase reaction, according to Eqs. () (with free energy changes at 1450°C), reported in other studies …”
Section: Resultssupporting
confidence: 55%
“…However, previous investigations showed that this reaction is not thermodynamically favored over the entire pyrolysis temperature range of the present study (1250°–1400°C) 62 . Therefore, formation of SiC proceeds rather via a solid–gas process, according to reaction () 2,61,62 . Further evidences for reaction () being active in the system are provided by (i) the fact that SiC was almost always found in close proximity to the graphitic regions (see Fig.…”
Section: Resultsmentioning
confidence: 49%
“…However, this reaction by itself is not sufficient to explain the growth mechanism of the nanowires, due to increased CO partial pressure, resulting from the precursor decomposition and from the byproduct of the reactions, which would make reaction () difficult to proceed 60 . Accordingly, the growth of the Si 3 N 4 nuclei formed should rather progress via a gas‐phase process following reaction (), as observed in other studies 52,54,57,60,61 …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation